A survey on the use of rugs in Australian horses. Issue 1 (27th November 2022) - Cox, EG; Bell, RJW; Greer, RM; Jeffcott, LB
Abstract : The practice of horse rugging has important implications for horse welfare and performance, but in Australia, rugging practices have not been properly documented. The objective of this study was to obtain an understanding of Australian horse rugging practices. An online survey reviewed the management of 2659 Australian horses over 12 months. Of the reported horses a total of 84.8% were rugged, although most owners (69.5%) indicated that they were unsure whether horses needed to be rugged at all. Rugging was felt by 59.8% of owners to be a requirement for horses in competition. Riding and competition were significantly associated with the use of rugs. Nearly all respondents (89.0%) felt that 'over‐rugging' was a concern. However, 4.8% of owners would use up to 4 rugs at any one time on their horse and 21.4% of horses were still rugged in temperatures above 20°C in Australia. Many Australian horse owners (42.8%) also believe that horses feel cold if they are not rugged. Anthropomorphism when it comes to rugging horses cannot be justified as the horse has a much wider thermoneutral zone (TNZ) than humans. Australian climate, owner opinions, equestrian discipline and whether a horse is used for riding influence Australian horse rugging practices. However, current practices are based on limited available research and are not necessarily to the benefit of the horse. The major limitation was that the survey likely attracted respondents who are interested in the topic creating a self‐selection bias.